Post-Myocardial Infarction Ventricular Septal Defect Successfully Treated with Impella as Bridge to Cardiac Transplantation - Lauren Giudicatti; Benjamin Silbert; Xiao-Fang Xu; Anthony Putrino; Felicity Lee; Amit Shah; Robert Larbalestier; Karim Slimani; Andrew Laycock; Kaitlyn Lam (Case Reports in Cardiology)
A 63-year-old female presented late with anterior ST-elevation myocardial infarction and cardiogenic shock. This was complicated by acute ventricular septal defect with large left-to-right shunt. An Impella CP was inserted on day seven with rapid haemodynamic improvement. This facilitated bridge to cardiac transplant on day twelve post-MI.